PENCIPTAAN FILM BABAN GALA: REPRESENTASI EKSPRESI PERSONAL SEBAGAI PANGHULU DI MINANGKABAU - Ikrar Fardila (Pascasarjana Institut Seni Indonesia Padang Panjang, 2020)
ABSTRACTBaban Gala isan audio visual workrelatedto personal expressionof a panghulu honorary title in Minangkabau. The title Panguluor Datuakis a hereditary title according to the Minangkabau customary Tambo based on maternal line age (matrilineal). Panghulu for the Minangkabau community has a great responsibility in managing their nephew in particular and the nagari (region) community in general. Carrying an honorary degree without being equipped with disciplines about customs, is a mental burdenon the environment. Based on that the author creates an audio visual artwork of fiction film type with the application of the concept of